Plant abiotic stress: a prospective strategy of exploiting promoters as alternative to overcome the escalating burden. Issue 1 (2nd January 2016) - Singhal, Parul; Jan, Arif Tasleem; Azam, Mudsser; Haq, Qazi Mohd Rizwanul
ABSTRACT: Plants being sessile are shaped by evolution to adapt themselves and tolerate various stresses, be it salinity stress, drought, high/low temperature in nature. They have evolved with every alternate strategy to tackle serious abiotic stresses through considerable degree of developmental plasticity, including adaptation via cascades of molecular networks. Understanding the mechanism of genes responsible for plant adaptation to environment will help in predicting the scenarios, expanding the genetic aspect of abiotic stress-regulating genes to protect and extrapolate the level of tolerance or vulnerability conferred in natural ecosystems. Complementing the agronomic need for greater tolerance to abiotic stress, studying plant abiotic stress response can help in gaining insight into plant biology that can be practically applied to unlock the secrets in order to improve plant productivity to feed the ever increasing population of human beings.